Гардемарины: [романы : в 2 кн.] (Н. М. Соротокина ; худож. В. Дугин) - Соротокина Нина Матвеевна (1994)
Экземпляры: КХ (19970531) / Инвентарный номер: 1020734 / Цена: 4275.00 / Сис.шифр: Р2 / Авт.знак: С 65 / ГРНТИ: 17 / ББК: 84(2)